TRADISI PENULISAN HASYIYAH DI DUNIA ISLAM - IRFAN SALIM (Al Qalam, 2012)
In the historical development of Islamic knowledge, there was one interesting and unique tradition, i.e. the tradition of writing by giving annotation toward a previous work, and then this annotation was annotated again by another author. The work that became a main source or reference, which was called matn, then was annotated in the farm of syarh, and this syarh, then, was given explanation, which was called hasyiyah or faotnotes to put the sources or detail explanation on main of syarh that were not included in the main text. There was also hamisy in the annotation. The function of hamisy was similar to the hasyiyah. While the hamisy was put in the flanks or borders of the book, the hasyiyah (footnotes) was put on the bottom of pages in a smaller fant of letters. However, if the annotation was considered too long, the other ulama summarize it in the farm of mukhtashar. It seems that these writing systems had been conducted from the fall of Islamic civilization until the twentieth century. One factor that caused this condition was the intellectual ignorance because of various external factors in the political process and political structure in that period so that it influenced the intellectual of some Muslim thinkers at the moment. They viewed that knowledge or science was finished, and what thry could do was to understand what had been inherited by previous generations. kaywords: hasyiyah, syarh, ta'liq